The Pengalaman Pengguna Aplikasi E-Absensi Berbasis IOS dan Kinerja Pegawai - fanro, fanro_2024 (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2025)
Employee attendance is an obligation, regulated in Government Regulation No. 94 of 2021 Article 4 letter f. January 2 2023 ASN and NON ASN North Bengkulu Regency Government are required to carry out IOS-based digital attendance. Various problems were encountered, such as difficulty accessing the attendance website, the network often having problems, so that employee attendance times were not synchronized, so the North Bengkulu Regency Government continued to develop applications (up-grade). The use of e-attendance applications should prevent the emergence of bureaucratic pathologies such as fraud that occurs in manual attendance so as to improve the quality of service and employee performance. The urgency of research is the sub-district's role as an extension of government services to the local community. The research aims to determine the influence of IOS-based e-attendance application users on employee performance. The research method uses quantitative and qualitative methods. The research results show that the data is normally distributed (kolmogoro-smirnove test). The r value is 0.801, meaning there is a positive and significant relationship between iOS-based e-attendance user experience and performance of 0.801. The effective contribution of e-attendance user experience to employee performance is 64.20%, 30.80% is influenced by other factors.